Avaliação da aplicação da farinha da palma forrageira (Opuntia ficus-indica) em pão de forma - Alves, Simone de Andrade (2019)
The forage palm (Opuntia ficus-indica) is a plant widely consumed in Mexico in human food and well adapted in regions with low rainfall, such as the Brazilian semiarid. In Brazil, this crop covers an area of approximately 600,000 hectares, only in the Northeast region. The objective of this study was to evaluate the application of this raw material in the preparation of bread form, with the intention of improving the nutritional content of this product so consumed in the daily life of the population, and thus encourage the consumption of this plant, which is underutilized, and which contains great nutritional value, mainly in relation to micronutrients, such as calcium (Ca), magnesium (Mg), potassium (K) and zinc (Zn) larger than that found in several vegetables. The flour was obtained and three loaves were formulated, replacing the wheat flour with a 5%, 10% and 15% palm flour fraction. The loaves were submitted to sensory analysis of 106 (one hundred and six) untrained judges who chose the bread loaf with 5% of palm flour as the most accepted, resulting in an acceptability index of 75%. Analyzes of total phenolic compounds and antioxidant activity were carried out using the ABTS • radical radical capture method, on the bread loaf with 5% of palm flour and the control bread. In the flour, these analyzes were performed at time zero, after two months and after six months of production. Compared to control bread, the palm flour increased the fiber and micronutrients content without altering the texturometric parameters (p <0.05), as well as promoting the bread of form, resistance to the multiplication of fungi characteristic of the aging of breads generally.